Community participation interventions for children and adolescents with a neurodevelopmental intellectual disability: a systematic review - Andrews, J.; Falkmer, Marita; Girdler, Sonya (Informa Healthcare, 2014)
Purpose: The purpose of this review was to examine the effectiveness of community integration interventions in facilitating the community participation, self-esteem, and quality of life of children and adolescent’s with a neurodevelopmental intellectual disability. Methods: Electronic searches of five databases and manual searches of reference lists were conducted. Community integration interventions which targeted friendship development, recreation participation, quality of life, and self-esteem were included. Results: Thirteen studies were included in this review. A variety of study designs and interventions were used. All but one study reported significantly increased friendships, five studies reported increased recreation participation and one study reported increased quality of life and self-esteem. Methodological quality of the studies ranged from adequate to strong.Conclusions: Community integration interventions appear to be effective in enhancing the inclusion of children and adolescents with a neurodevelopmental intellectual disability. In particular, findings from this review highlight that there are potentially many ways to continue to improve the effectiveness of community participation interventions for this group. These include the need for the development of programmes which facilitate friendships alongside recreational participation, include typically developing peers, consider the activity preferences of children and adolescents in developing programmes, and accommodate individual impairments and needs through grading and adaptive leisure activities. Future interventions should use the International Classification of Functioning, Disability and Health as a measurement framework and consider the role of factors such as impairment, personal and environmental factors in facilitating community participation. Implications for Rehabilitation 1.Community participation interventions appear to be effective in enhancing the inclusion of children and adolescents with neurodevelopmental intellectual disability. 2. Future community integration interventions should facilitate friendships alongside recreational participation, include typically developing peers, consider the activity preferences of children and adolescents in developing programme, and accommodate individual impairments and needs through grading and adaptive leisure activities. 3. The International Classification of Functioning, Disability and Health should be used as a measurement framework and consider the role of factors such as impairment, personal and environmental factors in facilitating community participation.